Development of an Economic Sociology E-Module Using the ADDIE Model to Improve Student Learning Outcomes - Ade Holisoh; Badrus Sholeh; Rusmaini Rusmaini (MASI Mandiri Edukasi, 2026)
The implementation of the Independent Learning Independent Campus (MBKM) policy requires transforming learning in higher education by providing innovative, contextually relevant teaching materials. However, learning in the Economic Sociology course in the Economics Education Study Program still relies on conventional teaching materials that are less interactive and do not optimally facilitate student learning. This study aimed to develop a valid, practical, and effective Economic Sociology e-module. This research employed a Research and Development (R&D) approach using the ADDIE model, consisting of analysis, design, development, implementation, and evaluation stages. The participants involved one material expert, one media expert, three lecturers, and 33 students of the Economics Education Study Program at Pamulang University. Data were collected through observations, interviews, questionnaires, and learning outcome tests. The results showed that the developed e-module was categorized as very valid based on assessments from media experts (90%) and material experts (91%). The practicality assessment indicated that the e-module was very practical based on lecturer responses (89%) and student responses (86%). Furthermore, the effectiveness test using a paired sample t-test demonstrated a significant improvement in student learning outcomes after using the e-module (p = 0.000 < 0.05). Therefore, the Economic Sociology e-module is considered valid, practical, and effective as a digital teaching material to support learning in higher education.